Computer Aided System Using Canny Edge for Long Bone Fracture Detection - Amir, Ahmad Akmal Qayyim; Ahmad, Ida Laila (Evolution in Electrical and Electronic Engineering, 2022)
Bone fracture is a common condition in humans that arises as a result of excessive pressure applied to the bone or as a result of a simple accident. Therefore an accurate bone fracture prognosis is critical in clinical situations. Image processing techniques are now widely used in a variety of applications. The image processing technique is used in fracture detection using image enhancement, image segmentation and feature extraction. This project used the canny edge detection method and Hough transform to assist in the fracture detection algorithm. Canny edge detection is deemed superior as it identifies thin edges in noisy images and can detect all existing edges in an image and is unaffected by noise. This project use Hough Transform for line detection in the sample image. The main aim of this project is to detect bone fractures from x-ray images. The algorithm is tested on sample images that have been provided. The suggested system is quite precise and efficient, according to the findings of several trials.